Licenciamento ambiental em postos de revenda de combustíveis à luz dos princípios constitucionais de defesas do meio ambiente: o caso do município de Natal/RN - Silva, Carlos Sérgio Gurgel da (2010)
This study approaches the question of the administrative procedure of the environmental licensing of ranks of fuel resale, taking as basis a study case of the reality of the City of Natal/RN (Brazil). For in such a way, it was done a retrospect on the evolution of the system of road transport in Brazil, having started to briefly analyze the urbanization process that if after accented in the capitals of the Brazilian States the decade of 1950, relating these subjects with the growth of the sector of fuel resale. After that, it was transferred boarding of the defense of the national environment to the light of ambient principles constitutional. In the sequence, a boarding on the ambient guardianship in the Federal Constitution of 1988 was made, treating basically specifies and on the national urban politics and the national politics of the environment, with its instruments. In the sequence, it was transferred the analysis of the abilities and attributions of the National Advice of the Environment (CONAMA) and its Resolutions, for then only enter in the most important part of this work: an analysis of the environmental licensing of ranks of fuel resale, in the reality of the City of Natal/RN. Before this specific boarding, it was proceeded specifically a survey and communication from the applicable norms to such establishments (Resolutions of the CONAMA and norms of the ABNT), for after that carrying through an geo-ambient characterization of the City of Natal/RN. Finally, a reflection was made on the possibility of magnifying of the state activity, in terms of guarantees for the responsible members for the environmental policy and of administrative efficiency, through the idea of the ambient regulation. For the accomplishment of this study, it was proceeded research in diverse sources such as books, magazines, sites of the Internet, periodicals, thesis and dissertations, among others material, beyond visits the agencies that direct or indirectly act with the ambient defense and as fuel resale, such as Secretariat of Environment and Urbanism of the City of Natal (SEMURB), Institute of Economic Development and Environment of RN (IDEMA), Brazilian Institute of the Environment and the Natural resources You renewed, Executive Management of RN (IBAMA/RN), Public prosecutor's office of the Environment of Natal (Public prosecution service of the RN), National Agency of Oil (ANP) and Union of the Retailing of Derivatives of Oil of the RN, among others. To the end, satiated regulation is observed that although on the substance of the ambient licensing in ranks of fuel resale, also with federal, state and municipal norms, the municipal Public Power is very far from the fulfilment of its institutional functions, in the question environmental policy of these establishments, a time that few are the permitted ranks of resale in the city of Natal/RN